Skin and soft tissue infection caused by Basidiobolus spp. in Australia. (2020) - Hung, Te-Yu; Taylor, Brooke; Lim, Aijye; Baird, Robert; Francis, Joshua R.; Lynar, Sarah
Abstract: Fungi from the order Entomophthorales are rare but well recognized cause of tropical fungal infection, typically causing subcutaneous truncal or limb lesions in immunocompetent hosts. They may also mimic malignancy by causing intrabdominal mass, sometimes resulting in obstructive gastrointestinal or renal presentations. A 4-year-old female presented with a progressively growing abdominal wall lesion over several months, developing into acute inflammation of the abdominal wall with systemic symptoms. She underwent surgical debridement and fungal culture of subcutaneous tissue was positive for Basidiobolus spp with characteristic histopathological findings. Treatment with voriconazole followed by itraconazole over a total duration of 6 weeks led to complete resolution. Basidiobolus spp is an unusual cause of infection with characteristic mycological and histopathological findings. Infection can present in a number of ways ranging from a slow-growing mass in the subcutaneous soft tissue to an invasive mass in the gastrointestinal tract. Identification of its unique beak-like zygospore and Splendore-Hoeppli phenomenon on histopathological specimens can be pathognomonic and could provide the key to early diagnosis. Review of the literature found that timely diagnosis and commencement of antifungal therapy can be curative with or without surgical treatment. Considering the rarity of this tropical infection, this case provides the opportunity for revision of the typical presentations and diagnostic findings of Basidiobolus spp. With early recognition and suitable treatment, outcomes are generally favorable.